Depressive symptoms predict cognitive decline and dementia in older people independently of cerebral white matter changes: the LADIS study - Verdelho, A.; Madureira, S.; Moleiro, C.; Ferro, J. M.; O’Brien, J. T.; Poggesi, A.; Fazekas, F.; Scheltens, P.; Waldemar, G.; Wallin, A.; Erkinjuntti, T.; Inzitari, D. (Journal of Neurology, Neurosurgery and Psychiatry, 2013)
Objective Depressive symptoms (DS) have been associated with increased risk of cognitive decline. Our aim was to evaluate the longitudinal influence of DS on cognition in independent older people, accounting for the severity of white matter changes (WMC). Methods The LADIS (Leukoaraiosis And DISability in the elderly) prospective study evaluated the impact of WMC on the transition of independent older subjects into disability. Subjects were evaluated annually over a 3 year period with a comprehensive clinical and neuropsychological evaluation. Previous episodes of depression and current DS were assessed during each interview. Severity of DS was assessed using the self-rated 15 item Geriatric Depression Scale. A neuropsychological battery and clinical criteria for cognitive impairments were applied in all clinical visits, and cognitive compound measures were made based on neuropsychological results. MRI was performed at baseline and at year 3. Results 639 subjects were included (74.1 +/- 5 years old, 55% women, 9.6 +/- 3.8 years of schooling). Dementia was diagnosed in 90 patients and cognitive impairment not dementia in 147 patients at the last clinical evaluation. DS were an independent predictor of cognitive impairment (dementia and not dementia) during follow-up, independent of the effect of the severity of WMC, medial temporal lobe atrophy, age, education or global cognitive function at baseline. Conclusions DS are associated with an increase risk of cognitive decline, independent of the effect of WMC, probably due to an additive or synergistic effect. In this context, DS probably represent a subtle ongoing organic dysfunction